The first step in an investigation of quantitative ultrasound as a technique for evaluating infant bone strength. Issue 2 (28th October 2020) - Soto Martinez, Miriam E.; Love, Jennifer C.; Crowder, Christian M.; Wiersema, Jason M.; Pinto, Deborrah C.; Derrick, Sharon M.; Gao, Si; Fleischman, Julie M.; Greeley, Christopher; Donaruma‐Kwoh, Marcella; Bachim, Angela
Abstract: This study's purpose is to evaluate whether bone speed of sound (SOS) data, a parameter of quantitative ultrasound, collected from an infant autopsy sample are comparable to data collected from healthy, living infants. We hypothesize that SOS values obtained from deceased term‐born infants will fall within the normal range for healthy, living infants. The study sample consists of 351 deceased infants between the ages of 30 weeks gestation at birth to 1 year postnatal at the time of death receiving autopsies at the Harris County Institute of Forensic Sciences or Texas Children's Hospital in Houston, TX. Various multivariate and univariate statistics were used to examine the relationship between SOS and age, prematurity, and chronic illness. The results of an ANOVA comparing the study sample data to published data from healthy, living infants indicate the SOS data are comparable. Additionally, a MANOVA indicated significant differences in SOS related to prematurity ( p = 0.001) and age ( p < 0.001). Mean SOS was significantly greater among term‐born infants (M = 3065.66, SD =165.05) than premature infants (M = 2969.71, SD =192.72). Age had a significant polynomial (cubic) relationship with SOS for both the premature and term groups ( p < 0.001). Results suggest that bone from an infant autopsy sample is an appropriate surrogate to examine the relationship between SOS and determinants of bone strength. Therefore, future research will use this study sample to investigate the relationship between SOS and determinants of bone strength in infants.